Forbush Decrease: A New Perspective with Classification - Raghav, Anil; Shaikh, Zubair; Bhaskar, Ankush; Datar, Gauri; Vichare, Geeta (My University, 2017)
Sudden short-duration decreases in cosmic ray flux, known as Forbush decreases (FDs), are mainly caused by interplanetary disturbances. A generally accepted view is that the first step of an FD is caused by a shock sheath and the second step is due to the magnetic cloud (MC) of the interplanetary coronal mass ejection (ICME). This simplistic picture does not consider several physical aspects, such as whether the complete shock sheath or MC (or only part of these) contributes to the decrease or the effect of internal structure within the shock-sheath region or MC. We present an analysis of 16 large (≥8%) FD events and the associated ICMEs, a majority of which show multiple steps in the FD profile. We propose a reclassification of FD events according to the number of steps observed in their respective profiles and according to the physical origin of these steps. This study determines that 13 out of 16 major events (∼81%) can be explained completely or partially on the basis of the classic FD model. However, it cannot explain all the steps observed in these events. Our analysis clearly indicates that not only broad regions (shock sheath and MC), but also localized structures within the shock sheath and MC have a significant role in influencing the FD profile. The detailed analysis in the present work is expected to contribute toward a better understanding of the relationship between FD and ICME parameters.
Keywords: Shock-sheath; Magnetic cloud (MC); ICME; Cosmic ray; Forbush decrease; Local magnetic structures